PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN (Studi Pada Pelanggan Pasta Gigi Formula berusia > 15 tahun di Kelurahan Bulusan dan Tembalang, Kecamatan Tembalang, Semarang) - Aprilia Pravianti Salim; Agus Hermani (Jurnal Ilmu Administrasi Bisnis, 2018)
Formula toothpaste as the first product produced by PT Orang Tua has become the mainstay of Indonesian family, to maintain oral health. However, in the midst of today's toothpaste competition, there are many low customer loyalty levels like not always buying Formula toothpaste, not subscribing, wanting to switch to another brand, and unwilling to recommend to the product. This is expected because the price is considered expensive and the quality of the product is considered poor. This study aims to determine the effect of price variables and product quality on customer loyalty toothpaste Formula. This type of research is an explanatory research, with sampling technique using purposive sampling technique. The sample in this study amounted to 112 respondents who are customers of Formula> 15 years old toothpaste in Bulusan and Tembalang, Tembalang District. Data collection techniques in this study through questionnaires. This research uses qualitative and quantitative analysis techniques. Quantitative analysis uses validity test, reliability test, correlation coefficient, simple and multiple regression analysis, determination coefficient, significance test, and tested using SPSS for Windows. The results of this study indicate that the variable price and product quality each have a significant influence, and positive on customer loyalty. Two variables have been tested in stages and together show that the price variable (0,277) and product quality (0.391) simultaneously have a moderate relationship to customer loyalty variables. The amount of contribution owned by the variable of product quality is greater than the amount of the variable price contribution, the coefficient of determination (R2) for the price variable is 7.7% and the product quality is 17.2%. To improve customer loyalty, the researcher's suggestion is, Formula toothpaste should still maintain an affordable price for its customers. To improve product loyalty, the researcher's suggestion is, it is necessary to improve product quality such as enhanced toothpaste, improved function so that it can solve the problem of tooth and mouth of customer more quickly and precisely, and longer mouth freshness after using toothpaste.